Potentials of non-ionic semi-rigid polymer assisted by cationic - Ainoon, Shabirin (2021)
A semi-rigid polymer, non-ionic Hydroxypropyl Cellulose (HPC) and its complex with cationic surfactant Benzyl-dimethyl-tridecyl-azanium Chloride (BZK) were characterized and investigated as a potential drag reduction agent (DRA) in a closed-loop liquid circulation system (pipe loop). The characterizations were carried out using Transmission Electron Microscopy (TEM) to view the HPC and HPC-BZK complex in solution, and a rheometer to determine its rheology characteristics. The turbulent drag reduction performances were carried out in the pipe loop using water as the transporting liquid to simulate a commercial pipeline. Each HPC and HPC-BZK complex was subjected to different degrees of turbulence (Re: 49540, 59448, 63694 and 70771), concentrations (200 ppm, 300 ppm, 500 ppm, 800 ppm, and 1000 ppm), and pipe lengths (testing sections:1, 2, 3 and 4 m). The TEM images showed that HPC particles were not physically interacting with each other and no inter-particle bridging was observed, whereas the TEM images of BZK confirmed the presence of micelles. Given HPC was non-ionic and BZK was cationic, not physical interaction was expected. However, the TEM images of HPC-BZK complex showed an image similar to a micro-emulsion which suggested a physical interaction that contradicted the initial expectation. The rheology data for both HPC and HPC-BZK complex showed that highest viscosity was obtained at the lowest shear rate and the lowest viscosity was obtained at the highest shear rate. Based on the rheology data, it was therefore expected that the highest drag reduction performances should be obtained at the lowest shear rate (minimal degree of turbulence, Re) and at the highest liquid viscosity. The results of the pipeline study were as follows: First, among the tested Re, moderate Re: 59448 produced the highest drag reduction performance for both HPC and HPC-BZK complex. Second, the highest concentration was observed to produce the highest drag reduction performance (1000ppm HPC and 1000-1000 ppm HPC-BZK complex). And third, both HPC and HPC-BZK complex were shown to display the highest drag reduction performance in the shortest pipe length (1m). Furthermore, it was observed that all the results indicated that HPC-BZK complex showed higher drag reduction performance than HPC. 1000-1000ppm showed up to 30.81% of drag reduction compared to 1000 ppm HPC which showed 27.24% of drag reduction in the 1 m pipe length when subjected to Re: 59448. The major difference between HPC-BZK complex and HPC was the presence of BZK, and the absence of any chemical interaction suggested that BZK attributed to the drag reduction enhancement between HPC and HPC-BZK complex. Overall, it was concluded that HPC is a potential drag reduction agent for pipe flow enhancement, and its drag reduction performance could be enhanced in the presence of BZK.